Developing an alcohol and other drug serious game for adolescents: considerations for improving student engagement. (4th August 2022) - Nicholas, Joanna; Mills, Brennen; Hansen, Sara; Bright, Stephen J.; Boyd, Heather; Brook, Luke; Watson, Jess; Hopper, Luke
Abstract: Objectives : To explore perceptions of alcohol and other drug (AOD) education and digital game design preferences among Australian adolescents with the goal of identifying key factors to promote engagement in an AOD serious game for Australian secondary school students. Methods : Semi‐structured focus groups were conducted with 36 adolescents aged between 13 and 18 years. Qualitative data was analysed using thematic analysis. Results : Participants described heightened engagement with AOD education that incorporated relatable and relevant real‐life stories and interactive discussions. They also expressed a desire for learning to focus on practical strategies to reduce AOD harm and overcome social pressure to use AOD. Participants highlighted the importance of incorporating relatable characters and context‐relevant scenarios in promoting engagement, and identified social elements, player choice, and optimal challenge as important game design considerations. Conclusions : A focus on meaningful realistic scenarios, relatable characters, relevant information and practical skills may promote high school aged students' engagement with AOD educational content. Game designs incorporating social elements and decision‐making opportunities may be conducive to promoting engagement and enhancing learning. Implications for public health : Findings from this study can be used by researchers and game designers for the development of future AOD serious games targeted at Australian adolescents.